Inuit Elder Policy Guidance for System-wide Educational Change in Nunavut, 2003-2013 - McGregor, Heather Elizabeth; McGregor, Catherine A. (University of Saskatchewan, 2020)
Elders have been educators and experts in the Arctic for as long as people have inhabited the region. The involvement of Elders in schools and school systems has a relatively shorter history, but is more significant than has been documented to date. Elder instruction, to teach language and/or to facilitate cultural content or “culture class” began as early as the 1970s in some Nunavut communities. By the year 2000 four Inuit Elder Advisors were working full-time for the Nunavut Department of Education (NDE) developing educational philosophy and other materials for schools, in collaboration with a pan-territorial Elders Advisory Committee (EAC), classroom teachers and curriculum staff. We argue that the active role of Elders at the territorial level of school system oversight was critical to achieving Nunavut’s aspirations for educational policy change in the years between 2000 and 2013. The article describes how this work was conducted in Nunavut, analyzes some of the outcomes and materials developed, and highlights the opportunities and complexities of working with Elders and Elder knowledge within contemporary institutions, such as school systems.